Knowledge of Midwives on IUD Counseling - Ferina Ferina; Benny Hasan Purwara; Elsa Pudji Setiawati; Hadi Susiarno; Muniroh Abdurrahman; Hadyana Sukandar (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2019)
The evaluation of IUD contraceptive services is still lack of quality until now. Many IUD acceptors choose to stop use contraception because they don't accept side effects such as bleeding, and fear of interfering with sexual intercourse. Adequate information from professional health personnel, in the form of counseling, is a very important step in helping women choose the best contraceptive method and according to their needs. The purpose of this study was to determine the relationship between education level and work period of midwives to the knowledge of midwives about IUD counseling. The research method uses a quantitative approach with a crossectional design. The number of respondents was 124 midwives Public Health Center in Bandung. The sampling technique uses consecutive sampling. Measurement of IUD counseling knowledge using a questionnaire that has been tested for validity and reliability using the Rasch Model with alpha chron-bach 0.87 (Good). Data were analyzed using SPSS 20 chi-square. The results of the study found that almost all of the 96% of respondents were lack of knowledge about counseling IUDs. The chi-square analysis results did not have a significant relationship between the level of education and knowledge of IUD counseling p = 0.548 (> 0.05). There is no significant relationship between the period of work with knowledge of IUD counseling p = 0.081 (> 0.05). Communication and counseling have been included in the Midwifery Diploma III education curriculum, but the level of education does not have a significant relationship to the knowledge of midwives about IUD counseling. This shows that the learning process in educational institutions has not been able to produce midwives who have knowledge of IUD counseling as expected.